Three Years Clinical Audit of Patients Presenting in Cornea Clinic at a Tertiary Care - Mazhar-ul-Hasan, Aziz-ur-Rehman, Nasir Bhatti, Muhammad Umar Fawad, Munawar Hussain, Umair Qidwai (Pakistan Journal of Ophthalmology, 2011)
Purpose: To determine the mode of presentation and aetiology of patients presenting in cornea clinic at a tertiary care teaching hospital in Karachi. Material and Methods: This hospital based retrospective case study was conducted in Al-Ibrahim Eye Hospital Karachi from 1st January 2008 to 1st January 2011. Results: A total of 2213 new patients (1347 males and 866 females) presented in cornea clinic. The average age at presentation was 59.5 years. The most common disease was Microbial Keratitis followed by Spheroidal degeneration in 230 (10.39%) and Keratoconusin 178 (8.01%) patients. Conclusion: Corneal diseases are common in the population studied with Microbial Keratitis as the most common condition. Health-promotion strategies have to be developed and implemented to raise awareness about the causes and prevention of corneal blindness.